2012
DOI: 10.1002/ijc.27767
|View full text |Cite
|
Sign up to set email alerts
|

Distinct tumor protein p53 mutants in breast cancer subgroups

Abstract: Tumor protein p53 (TP53) is mutated in approximately 30% of breast cancers, but this frequency fluctuates widely between subclasses. We investigated the p53 mutation status in 572 breast tumors, classified into luminal, basal and molecular apocrine subgroups. As expected, the lowest mutation frequency was observed in luminal (26%), and the highest in basal (88%) tumors. Luminal tumors showed significantly higher frequency of substitutions (82 vs. 65%), notably A/T to G/C transitions (31 vs. 15%), whereas molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 24 publications
4
79
0
2
Order By: Relevance
“…This rate is approximately 80% in basal-like cancers while it is reported to be less than 15% in luminal breast cancers (Sørlie et al, 2001). In a study evaluating 572 patients, the rate of p 53 mutation was 26% and 88% in the luminal group and the basal-like group, respectively (Durnay et al, 2013). The rate of p 53 mutation was 44% and 28% in the TNBC group and the NTNBC group, respectively, and the difference between these two groups were statistically significant (p=0.001).…”
Section: Discussionmentioning
confidence: 98%
“…This rate is approximately 80% in basal-like cancers while it is reported to be less than 15% in luminal breast cancers (Sørlie et al, 2001). In a study evaluating 572 patients, the rate of p 53 mutation was 26% and 88% in the luminal group and the basal-like group, respectively (Durnay et al, 2013). The rate of p 53 mutation was 44% and 28% in the TNBC group and the NTNBC group, respectively, and the difference between these two groups were statistically significant (p=0.001).…”
Section: Discussionmentioning
confidence: 98%
“…Overall, these results suggest that in estrogen receptor-positive tumors, [55][56][57][58][59] These studies have also shown that in a given population, the incidence of luminal A tumors is 48-58%, luminal B tumors is 19-25%, triple negative tumors is 11-23%, and HER2-positive tumors is 5-11%. [55][56][57][58][59] Based on this type of classification, analysis of the frequencies of the sub-groups in our data set has shown that 129 (50%) are luminal A, 75 (29%) are luminal B, 37 (14%) are triple negative, and 15 (6%) are HER2-positive tumors. There was insufficient information for 52 samples to classify them into one of the sub-groups, as either ER, PgR, or HER2 expression data were not available.…”
Section: Phosphorylated Ntrk1 At Y674/y675 and Ptpn6 Expression In Esmentioning
confidence: 81%
“…This has enabled the distinction of different molecular subtypes in breast cancer (25), and their identification make it possible to select a specific treatment strategy and to better predict the prognosis (6). Approximately 70% of all breast cancers diagnosed in the USA are ER + (22,36).…”
Section: A) Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%
“…A molecular form includes genetic analysis as chromosomes 6, 7, 21 or molecular biotechnology, using biological markers as estrogen receptor (ER In addition, other factors can be analyzed that can be originated in the cancer cell itself as mutations in p53, EGFR or influenced by microenvironment as pH and MMP9 (6,7). According to some gene expression profile studies five different subtypes have been identified (8,9) …”
Section: Introductionmentioning
confidence: 99%